Macrostomia: A Review of Evolution of Surgical Techniques - Srikanth Gunturu; Ranganadh Nallamothu; Rama Mohan Kodali; Koteswara Rao Nadella; Leela Krishna Guttikonda; Vijayalakshmi Uppaluru (Case Reports in Dentistry)
Macrostomia is a congenital deformity resulting from failure of fusion of maxillary and mandibular process. It is a rare congenital deformity with an incidence of 1 in 60,000 to 1 in 300,000 live births. Transverse facial clefts are more common on right side of face in unilateral cases. Males are more affected than females. Various surgical techniques have been described in the literature for the correction of these defects. We report a case of macrostomia corrected with Z-plasty closure for skin, overlapping muscle closure, and triangular mucosal flap for commissure, with a review on existing techniques.